An Interventional Study (Calcium Supplementation & Health Education) On Premenstrual Syndrome - Effect on Premenstrual and Menstrual Symptoms - Shailesh Sutariya; Nitiben Talsania; Chintul Shah; Mitesh Patel (Medsci Publications, 2011)
The study was conducted to study the effect of calcium supplementation on Premenstrual and Menstrual Symptoms. It was a one-year follow-up prospective, randomized controlled interventional study. After the initial 2-cycle screening phase, a total of 215 healthy premenopausal women were enrolled in the study group calcium supplementation (500 BD) of the trial and 140 subjects either the relatives or neighbors of the study population were enrolled as control group health, nutrition, hygiene education of the trial. By the second and third treatment months, all symptoms except for fatigue and insomnia showed a significant response to calcium. For the symptom of low backache, the mean screening score was significantly higher than the control group score (0.82±0.74 vs 0.69±0.66, p=0.033) and became significantly lower than the control group score by the end of third treatment cycle. (0.30±0.45 vs 0.49±0.59, p<0.01). Nearly half (55%) of the women in the study group reported ≥50% improvement and one-third (30%) of the women in study group reported ≥75% improvement. Significantly lower symptoms score was detected in the urban sites during the first treatment phase with calcium and during the final treatment phase.